Helping boys at-risk of criminal activity: qualitative results of a multi-component intervention - Brennan Erin; Kenny Meghan; Lipman Ellen L; O'Grady Susanne; Augimeri Leena (BMC, 2011)
Abstract Background This qualitative study examines parent and child experiences of participation in a multi-component community-based program aimed at reducing offending behaviour, and increasing social competence in boys 6 to 11 years old in Hamilton, Ontario, Canada. The program builds on the concept of crime prevention through social development, and includes structured groups for the identified boy, parents, and siblings. Methods A sample of 35 families participating in the multi-component program took part in the qualitative study. Individual interviews with the boys, parents and siblings asked about changes in themselves, relationships with family and peers, and school after the group. Interviews were taped, transcribed and content analysis was used to code and interpret the data. Results Parents reported improvement in parenting skills and attainment of more effective communication skills, particularly with their children. Parents also found the relationships they formed with other parents in the program and the advice that they gained to be beneficial. Boys who participated in the program also benefited, with both parents and boys reporting improvements in boys' anger management skills, social skills, impulse control, and ability to recognize potentially volatile situations. Both parents and boys described overall improvement in family relationships and school-related success. Conclusions The qualitative data revealed that parents and boys participating in the multi-component program perceived improvements in a number of specific areas, including social competence of the boys. This has not been demonstrated as clearly in other evaluations of the program.